Expression of Cckbr, Gast, Reg1α, Tgfb1 genes in rat pancreas upon long-term hypoacidity and with administration of multiprobiotic «Symbiter® acidophilic» concentrated - Vakal, S.E.; Dvorshchenko, K.O.; Dranitsina, A.S.; Borodina, T.V.; Ostapchenko, L.I. (Вiopolymers and Cell, 2012)
Aim. Determination of the Cckbr, Gast, Reg1α and Tgfb1 genes expression in rat pancreas upon long-term hypoacidity and with administration of multiprobiotic «Symbiter® acidophilic» concentrated. Methods. Experiments were carried out on white non-strain mail rats. Hypoacidic state was modeled through intraperitoneal injection of omeprazole during 28 days. Level of genes expression was determined by semi-quantitative RT-PCR. Results. The elevation of levels of Cckbr, Reg1α and Tgfb1 mRNAs, as well as the appearance of Gast gene expression in rat pancreas upon hypoacidic conditions were shown. The levels of Cckbr and Tgfb1 mRNAs with administration of multiprobiotic «Symbiter® acidophilic» concentrated under the same conditions were similar to the control, while the expression of Gast gene was not detected; at the same time, the level of Reg1α mRNA was higher than that in animals with hypoacidity. Conclusions. Long-term hypoacidity is accompanied by changes in the expression of Cckbr, Gast, Reg1α and Tgfb1 genes in rat pancreas, while upon administration of multiprobiotic «Symbiter® acidophilic» concentrated the pattern of expression for most of the studied genes is similar to the control.
Keywords: hypoacidity, pancreas, gene expression, multiprobiotics. Мета. Дослідити експресію генів Cckbr, Gast, Reg1α і Tgfb1 у підшлунковій залозі щурів за умов тривалої гіпоацидності та при введенні мультипробіотика «Симбітер® ацидофільний» концентрований. Методи. Досліди проведено на білих нелінійних щурах-самцях. Гіпоацидний стан моделювали інтраперитонеальним введенням омепразолу протягом 28 діб. Рівень експресії генів визначали напівкількісним аналізом за допомогою ЗТ-ПЛР. Результати. Показано зростання рівня мРНК Cckbr, Reg1α і Tgfb1, а також появу експресії гена Gast у підшлунковій залозі щурів за гіпоацидних умов. При введенні мультипробіотика «Симбітер® ацидофільний» концентрований за тих самих умов вміст мРНК Cckbr та Tgfb1 виявився на рівні контрольних значень, експресії гена Gast не зафіксовано, а рівень мРНК Reg1 αперевищував цей показник тварин з гіпоацидним станом. Висновки. Стан тривалої гіпоацидності супроводжується зміною експресії генів Cckbr, Gast, Reg1α і Tgfb1 у підшлунковій залозі щурів, тоді як при введенні мультипробіотика «Симбітер® ацидофільний» патерн експресії більшості з досліджених генів подібний до контролю.
Ключові слова: гіпоацидність, підшлункова залоза, експресія генів, мультипробіотики. Цель. Исследовать экспрессию генов Cckbr, Gast, Reg1α и Tgfb1 в поджелудочной железе крыс в условиях длительной гипоацидности, а также при введении мультипробиотика «Симбитер® ацидофильный» концентрированный. Методы. Исследования проведены на белых нелинейных крысах-самцах. Состояние гипоацидности моделировали интраперитонеальным введением омепразола в течение 28 дней. Уровень экспрессии генов определяли полуколичественным анализом с помощью ОТ-ПЦР. Результаты. Показано повышение уровня мРНК Cckbr, Reg1α и Tgfb1, а также появление экспрессии гена Gast в поджелудочной железе крыс в гипоацидных условиях. При введении мультипробиотика «Симбитер® ацидофильный» концентрированный в тех же условиях содержание мРНК Cckbr и Tgfb1 оказалось на уровне контрольных значений, экспрессия гена Gast не зафиксирована, а уровень мРНК Reg1α превышал этот показатель у животных с гипоацидным состоянием. Выводы. Состояние длительной гипоацидности сопровождается изменением экспрессии генов Cckbr, Gast, Reg1α и Tgfb1 в поджелудочной железе, тогда как при введении мультипробиотика «Симбитер® ацидофильный» концентрированный паттерн экспрессии большинства исследованных генов близок к контролю.
Ключевые слова: гипоацидность, поджелудочная железа, экспрессия генов, мультипробиотики.